Insights by which TUDCA is a potential therapy against adiposity - Freitas, Israelle Netto; da Silva Jr, Joel Alves; Oliveira, Kênia Moreno de; Lourençoni Alves, Bruna; Dos Reis Araújo, Thiago; Camporez, João Paulo; Carneiro, Everardo Magalhães; Davel, Ana Paula (Frontiers in Endocrinology, 2023)
Adipose tissue is an organ with metabolic and endocrine activity. White, brown and ectopic adipose tissues have different structure, location, and function. Adipose tissue regulates energy homeostasis, providing energy in nutrient-deficient conditions and storing it in high-supply conditions. To attend to the high demand for energy storage during obesity, the adipose tissue undergoes morphological, functional and molecular changes. Endoplasmic reticulum (ER) stress has been evidenced as a molecular hallmark of metabolic disorders. In this sense, the ER stress inhibitor tauroursodeoxycholic acid (TUDCA), a bile acid conjugated to taurine with chemical chaperone activity, has emerged as a therapeutic strategy to minimize adipose tissue dysfunction and metabolic alterations associated with obesity. In this review, we highlight the effects of TUDCA and receptors TGR5 and FXR on adipose tissue in the setting of obesity. TUDCA has been demonstrated to limit metabolic disturbs associated to obesity by inhibiting ER stress, inflammation, and apoptosis in adipocytes. The beneficial effect of TUDCA on perivascular adipose tissue (PVAT) function and adiponectin release may be related to cardiovascular protection in obesity, although more studies are needed to clarify the mechanisms. Therefore, TUDCA has emerged as a potential therapeutic strategy for obesity and comorbidities.